Description of secondary flow in a subsonic turbine - D.O.C. Sá; L.M.C. Gato (Results in Engineering)
Secondary flows introduce unwanted kinetic energy losses in turbomachinery flows. These flows arise from the interaction of wall boundary layers when guide vanes or rotor blades deflect the main flow. While various models have been proposed to describe secondary flows in axial-flow turbines, the literature lacks a clear explanation of how the horseshoe vortex develops near the shroud. This paper presents results from three-dimensional flow simulations using a Reynolds-averaged Navier-Stokes equations solver to identify secondary flows in guide-vane and rotor-blade passages. The research focuses on the 1.5-stage RTWH Aachen axial turbine, which operates under subsonic conditions. The study successfully detected and visualised secondary flows within the turbine passages, enhancing our understanding of the development of horseshoe vortices near the shroud and how blade tip clearance influences this process.